Structural and functional studies on the chromatin and nucleosome binding proteins - Chodaparambil, Jayanth Velandy, author; Luger, Karolin, advisor (Colorado State University. Libraries, 2007)
The approximately two meters of eukaryotic DNA are compacted within the confines of the nucleus by hierarchical packing with an equal amount of histone proteins to form chromatin. The nucleosome is the fundamental repeating structural unit of chromatin. The nucleosome is the fundamental repeating structural unit of chromatin. Highly compacted DNA is very accessible to the transcription machinery. To understand the mystery behind the two opposing functions of the chromatin, it is essential for us to study nucleosome and chromatin structure in detail.

Higher order structure of chromatin has been an enigma for decades. Even though the nucleosome core particle has been intensively studied, the molecular mechanisms by which chromatin compaction takes place are poorly understood. One single nucleosome has a total accessible surface area of 28004Å2. A single cell contains thousands of nucleosomes, which translates to abundant surface area (in square meters) for trans-acting proteins to interact with. An intriguing problem arises from the need to arrange these surfaces in a way that leaves them accessible to trans acting proteins while fitting them in the cell's nucleus that is only 10-6 m in diameter.

Using biophysical and biochemical techniques, we studied the mode of interaction of the trans acting Kaposi Sarcoma Herpes Virus protein LANA to the nucleosome. We show that a peptide derived from the very N-terminus of the ~ 1000 amino acid long LANA protein cannot bind to individual histones, but only binds to H2A-H2B dimers or fully intact nucleosomes. The dimerization of H2A-H2B histories within the nucleosome leads to formation of a uniquely charged surface with which LANA interacts. This study thereby provides the first account of a protein directly and specifically interacting with the nucleosomal surface.

We further use the LANA and H4 tail peptides, which are both known to bind to the same surface of the nucleosome as molecular tools to show that the surface itself plays an important role in chromatin compaction. We show that a charged surface on the nucleosome acts as a repulsive domain that is modulated by tails and transacting proteins in chromatin compaction.

In an independent study, we investigate the histone chaperone nucleosome assembly protein 1 of yeast (yNAP1). We report three novel functions of this protein that are distinct from its histone chaperone function. Using biochemical techniques we show that yNAP1 can exchange historic dimers into preformed nucleosomes. During this process, yNAP1 can also slide nucleosomes assembled on longer DNA. We use a combination of analytical ultracentrifugation and atomic force microscopy to show that yNAP1 can facilitate the cleaning up of poorly assembled nucleosomal arrays. Using biochemical and biophysical techniques we show that the C-terminal acidic domain (CTAD) is essential for the ability of yNAP1 to remove histories from DNA and chromatin.
Keywords: chromatin; histones; Kaposi's sarcoma-associated herpesvirus; nucleosomes; proteins; molecular biology; biochemistry; biophysics